Association Mapping of Resistance to Yellow Rust in Winter Wheat Cultivars and Elite Genotypes. Issue 2 (1st March 2014) - Tadesse, W.; Ogbonnaya, F.C.; Jighly, A.; Nazari, K.; Rajaram, S.; Baum, M.
ABSTRACT: Yellow (stripe) rust, caused by Puccinia striiformis f.sp. tritici ( Pst ), is a destructive disease of wheat ( Triticum aestivum L.) all over the world, particularly in the Central and West Asia and North Africa (CWANA) region. Host plant resistance is the most economical and environment friendly approach to combating wheat rusts through the deployment of resistant cultivars. In this study, we report findings from an association mapping (AM) study of resistance to Pst in 167 facultative/winter elite wheat genotypes. The genotypes were evaluated for resistance to yellow rust (YR) at the adult plant stage and other agronomic traits for 2 yr (2011–2012) at ICARDA field station, Tel Hadya, Syria. The same genotypes were genotyped using 3051 diversity array technology (DArT) markers of which 1586 were of known chromosome positions. Out of the 167 genotypes evaluated for YR resistance, 65 genotypes (38.9%) were resistant, 20 genotypes (12%) were moderately resistant, 30 genotypes (18%) were moderately susceptible, and 52 genotypes (31.1%) were susceptible. Elite genotypes with high yield potential and YR resistance were identified and have been distributed to the National Agricultural Research System (NARS) for potential direct release and/or use as parents after local adaptation trials by the respective countries. Further, AM analysis using a mixed linear model (MLM), corrected for population structure and kinship relatedness and adjusted for false discovery rate (FDR), identified five genomic regions located on wheat chromosomes 2BL, 4BS, 6AS, 6BL, and 7BL which are significantly associated with genes conferring resistance to YR. The loci located on chromosome 4BS appeared to be a novel quantitative trait loci (QTL). These loci may be useful for choosing parents and incorporating new YR resistance genes into locally adapted wheat cultivars.